Dynamic response of a NACA0009 hydrofoil under cavitation conditions. Issue 6 (March 2019) - Wang, W; Zhou, L J; Wang, Z W; Escaler, X; De La Torre, O; Kang, W Z
Abstract: The dynamic response of an hydraulic machine is greatly affected by the water due to the added mass effect. However, the presence of cavitation can change the modal response of the coupled fluid-structure system because it modifies the properties of the surrounding fluid, i.e. the speed of sound and density. In this paper, a FEM-based acoustic-fluid model has been used to simulate the dynamic response of a NACA0009 hydrofoil with attached leading edge cavitation. The natural frequencies and the corresponding mode shapes have been compared for the hydrofoil in air, in still water and in cavitation conditions. The numerical predictions show a good agreement with the experimental results obtained in a high-speed cavitation tunnel. They confirm that different fluid conditions can modify the mode shapes in comparison with the modes in air. The nodal lines of the torsion and the second bending modes are slightly shifted with water and cavitation. Furthermore, the third mode of vibration under cavitation conditions appears as a combination of the torsion and the second bending shapes. The results indicate that such alterations are mainly induced by the value of the speed of sound inside the cavity.